2017
DOI: 10.1016/j.envres.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mammary histology and transcriptome profiles by low-dose exposure to environmental phenols at critical windows of development

Abstract: Exposure to environmental chemicals has been linked to altered mammary development and cancer risk at high doses using animal models. Effects at low doses comparable to human exposure remain poorly understood, especially during critical developmental windows. We investigated the effects of two environmental phenols commonly used in personal care products – methyl paraben (MPB) and triclosan (TCS) – on the histology and transcriptome of normal mammary glands at low doses mimicking human exposure during critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…These chemicals have been used as preservatives in personal care products, pharmaceuticals, and food additives, and have been found to promote cell growth through multiple mechanisms, including estrogenicity (Gonzalez et al 2018, 2019; Okubo et al 2001) and epidermal growth factor receptor signaling (Pan et al 2016). Particularly relevant to our findings of the greatest methyl and ethyl paraben disparities in the youngest non-Hispanic Black women was the finding that early life paraben exposures can alter developing mammary gland morphology and induce gene expression that resembles an early cancer-like state (Gopalakrishnan et al 2017). Use of hair products has been identified as a potential risk factor for breast cancer in non-Hispanic Black women (Stiel et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…These chemicals have been used as preservatives in personal care products, pharmaceuticals, and food additives, and have been found to promote cell growth through multiple mechanisms, including estrogenicity (Gonzalez et al 2018, 2019; Okubo et al 2001) and epidermal growth factor receptor signaling (Pan et al 2016). Particularly relevant to our findings of the greatest methyl and ethyl paraben disparities in the youngest non-Hispanic Black women was the finding that early life paraben exposures can alter developing mammary gland morphology and induce gene expression that resembles an early cancer-like state (Gopalakrishnan et al 2017). Use of hair products has been identified as a potential risk factor for breast cancer in non-Hispanic Black women (Stiel et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…Hence our rst objective was to adapt the TNBS chronic colitis model to young rats, with low mortality and signi cant brosis before reaching adult age. The window of opportunity was narrow, since in Sprague-Dawley rats the peri-natal period lasts until Postnatal Day 21 (PND 21), the pre-pubertal period until PND 42 (6 weeks) and the pubertal period until PND 63 (9 weeks) (13). We chose to induce colitis starting at 5 weeks of age and all rats were analyzed at 8 weeks of age, before the end of the pubertal period.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work on rats exposed to an environmental dose of triclosan (0.05 mg/kg/day) during a long period, from birth PND1 to reproductive stage and lactation (PND146), showed different results. Triclosan induced morphological changes of the mammary gland by increasing adipose tissue and decreasing the proportion of lobular tissue, but further transcriptomic and gene set enrichment analysis showed that genes upregulated by triclosan treatment during that exposure were homologous to genes downregulated in breast cancer in humans; conversely, genes downregulated by triclosan are homologous to certain genes upregulated in breast cancer [ 68 ]. These results suggest that the model species, timing of exposure, and/or dose can have significantly different effects; further studies should be undertaken to better understand how triclosan can affect the development of breast cancer.…”
Section: Edcs and Breast Cancermentioning
confidence: 99%